Mantiq Greek Menurut Pandangan al-Imam al-Ghazzali (M. 505 H./1111 M.) - Hamat, Mohd Fauzi (Jurnal Usuluddin, 1997)
This article discusses al-Ghazzalis point of view, a great Muslim thinker, on logic (Mantiq) Ghazzalis general opinion on Mantiq is discussed as well on his observation to Mantiq role in human knowledge.